Clinical and microbiological epidemiology of Candida infections in a high-complexity hospital in Tolima, Colombia (2014–2024) - Rafael A. Ramírez-Trujillo; Paula Carvajal-Hernández; Ángel González (PLoS ONE, 2026)
Background Candida spp. infections are an increasing challenge in high-complexity hospitals, yet epidemiological data remain scarce in underrepresented in Colombian regions such as Tolima. Methods We conducted a retrospective observational study in a high-complexity hospital in Ibagué (Tolima, Colombia) from 2014 to 2024, integrating two institutional data sources: administrative/clinical records and the microbiology laboratory database (WHONET). Species identification relied on culture and VITEK, and antifungal susceptibility was interpreted using criteria from the Clinical and Laboratory Standards Institute (CLSI) and the European Committee on Antimicrobial Susceptibility Testing (EUCAST). We summarized data using frequencies/proportions and medians (IQR), explored patterns with multiple correspondence analysis (MCA), and estimated associations with candidemia using penalized multivariable logistic regression due to low event frequency. Results We identified 987 candidiasis episodes and 776 fungal isolates, of which 314 were Candida (40.46%). Mucocutaneous disease predominated (vulvovaginal 50.7%; oropharyngeal 24.3%), while candidemia represented 2.0% of episodes. Among isolates, Candida albicans was most frequent (58.9%), followed by C. parapsilosis (16.6%), C. tropicalis (12.1%), and Nakaseomyces glabratus (6.4%); Candida auris was detected once. In exploratory clinical/administrative models, clinically recorded candidemia showed associations with invasive devices (OR 5.54, 95% CI 2.01–15.64), recent surgery (OR 7.11, 95% CI 1.20–30.88) and tumor (OR 19.88, 95% CI 3.14–97.51). Susceptibility data were available for 196/314 isolates (62.4%); echinocandin activity was high, whereas azole susceptibility was more variable. Conclusions Candidiasis showed a sustained recorded burden and substantial non- albicans diversity, supporting local surveillance, species-level identification, and isolate-level susceptibility testing.